Паразитические черви чаек (Lari) бассейна Верхнего Днестра - Сергиенко, М.И. (Вестник зоологии, 1971)
In the Upper Dniester basin when dissecting 249 individuals of Larus birds of the
following four species: Larus ridibundus, Chlidonias nigra, Ch. leucoptera and Sterna
hirundo 20 species of parasitic worms were found. High extensity and intensity of birds'
invasion with such species as Prosthogonimus ovatus, Diplostomum spathaceum, Cotylurus pileatus, Renicola lari, Paricterotaenia porosa, Aploparaksis larina, Tetrameres fissispina were observed. Invasion of birds with Echinostoma revolutum, Tanaisia fedtschenkoi,
Diplostomum flexicaudum, Ligula intestinalis is less frequent. In spring and autumn the
degree of gulls' invasion with helminths is lower than in summer. Eight species out of the
found parasites evoke in poultry and food-fish outbreaks of epizootics which in mass infestation have lethal result.